CORRELATION OF SERUM BILIRUBIN, GLYCEMIC CONTROL AND ALBUMINURIA IN TYPE 2 DIABETES MELLITUS – A RETROSPECTIVE STUDY - S. V. MYTHILI; S. SRIDEVI; A. J. MANJULA DEVI; V. S. KALAI SELVI; B. SHANTHI (International Journal of Pharma and Bio Sciences, 2013)
Bilirubin, a product of the heme catabolic pathway was considered as a toxic compound for many years.But the recent studies show that mildly elevated bilirubin levels are beneficial and negatively associated with the oxidative stress Serum bilirubin has been consistently shown to be negatively correlated to cardiovascular diseases (CVD), diabetes mellitus (DM), metabolic syndrome, and obesity. Recent studies are showing that bilirubin is negatively correlated with renal dysfunction and glycemic control, Hemoglobin A1c (HbA1c) in Diabetic individuals. To explore this further, we did a retrospective observational study. To assess the renal function albumin-creatinine ratio (ACR) was used as a marker and to assess glycemic control HbA1c was used as a marker. After statistical analysis we demonstrated the following; Negative association between bilirubin and HbA1c Negative association between bilirubin and albuminuria Positive association between glycemic control and albuminuria.